Type 1 Diabetes Genetic Risk Score: a novel tool to discriminate monogenic and type 1 diabetes - Patel, K A (Diabetes, 2016)
Distinguishing patients with monogenic diabetes from Type 1 diabetes (T1D) is important for correct diagnosis, treatment and to select patients for gene discovery studies. We assessed whether a T1D genetic risk score (T1D-GRS) generated from T1D-associated common genetic variants provides a novel way to discriminate monogenic diabetes from T1D. The T1D-GRS was highly discriminative of proven MODY (n=805) and T1D (n=1963) (ROC-AUC=0.87). A T1D-GRS of >0.280 (>50(th) T1D centile) was indicative of T1D (94% specificity, 50% sensitivity). We then analyzed the T1D-GRS in 242 White-European patients with neonatal diabetes (NDM) who had been tested for all known neonatal diabetes genes. Monogenic NDM was confirmed in 90%, 59% and 8% in patients with GRS <5(th) T1D centile, 50-75(th) T1D centile and >75(th) T1D centile, respectively. Applying a GRS 50(th) T1D centile cut-off in 48 NDM patients with no known genetic cause, identified those most likely to have a novel monogenic etiology by highlighting patients with probable early-onset T1D (GRS >50(th) T1D centile) who were diagnosed later, had less syndromic presentation but had additional autoimmune features compared to proven monogenic NDM. The T1D-GRS is a novel tool to improve the use of biomarkers in the discrimination of monogenic diabetes from T1D.